2018
DOI: 10.1186/s12889-018-6019-z
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of non-steroidal anti-inflammatory drugs consumption in Spain. The MCC-Spain study

Abstract: BackgroundNon-steroidal anti-inflammatory drugs (NSAIDs) are widely used despite their risk of gastrointestinal bleeding or cardiovascular events. We report the profile of people taking NSAIDs in Spain, and we include demographic factors, health-related behaviours and cardiovascular disease history.MethodsFour thousand sixtyparticipants were selected using a pseudorandom number list from Family Practice lists in 12 Spanish provinces. They completed a face-to-face computerized interview on their NSAID consumpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 20 publications
(33 reference statements)
2
16
0
1
Order By: Relevance
“…As in our study, studies from Norway and Spain observed that NSAIDs use decreased with age [11,29]. This complies with guidelines recommending avoiding NSAIDs for pain management in older adults whenever possible, due to high concerns of gastrointestinal hemorrhage, cardiovascular events, and renal impairment [7,30].…”
Section: Nsaidssupporting
confidence: 90%
See 1 more Smart Citation
“…As in our study, studies from Norway and Spain observed that NSAIDs use decreased with age [11,29]. This complies with guidelines recommending avoiding NSAIDs for pain management in older adults whenever possible, due to high concerns of gastrointestinal hemorrhage, cardiovascular events, and renal impairment [7,30].…”
Section: Nsaidssupporting
confidence: 90%
“…Adverse effects associated with opioids, such as constipation, respiratory depression, and addiction, can present a barrier to longterm treatment [8]. In recent years, the topic of analgesics use has received much attention in Europe [9][10][11][12][13][14]. However, the existing drug utilization studies, done on analgesics use in the older German population, either include only nursing home residents [15,16] or multi-morbid older adults [17], or focus on selected analgesics [13,18].…”
Section: Introductionmentioning
confidence: 99%
“…Pre-admission NSAID use was lower in older age groups, which is in line with a recent European study of NSAID epidemiology [22]. NSAIDS account for 25% of adverse drug events reported in the United Kingdom [23], and it is thought that the elderly are more susceptible to the adverse effects of these drugs [4].…”
Section: Discussionsupporting
confidence: 71%
“…The prevalence of regular NSAIDs consumption in the United States population has grown in recent decades, reaching values of 10.4, 11.8, and 4.4% for aspirin, non-aspirin and multiple NSAIDs, respectively [160]. Data from other countries, such as Spain, revealed higher prevalences of consumption (11.2 and 29.6% for aspirin and non-aspirin NSAIDs, respectively) [161]. However, NSAIDs consumption varies, depending on different factors, such as ethnic group, age, or sex [160,161].…”
Section: Musculoskeletal System Drugs That May Affect Hydration Stmentioning
confidence: 99%
“…Data from other countries, such as Spain, revealed higher prevalences of consumption (11.2 and 29.6% for aspirin and non-aspirin NSAIDs, respectively) [161]. However, NSAIDs consumption varies, depending on different factors, such as ethnic group, age, or sex [160,161]. Likewise, self-medicated NSAIDs consumption is widespread [162], regardless of the age group, including the polymedicated elderly and other population groups, including athletes.…”
Section: Musculoskeletal System Drugs That May Affect Hydration Stmentioning
confidence: 99%